Preparation method of preset jointed rock test piece
By pre-installing jointed microcrystalline wax medium in rock-like specimens and removing the media through specific processing steps, the problem of difficult to prepare jointed rock-like specimens in the prior art is solved, and the internal jointing form of the specimens is realized. Controllability and depth and breadth of research.
Patent Information
- Application Number
- CN202411695258.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-07
AI Technical Summary
It is difficult to prepare joint-like rock specimens with joints at low cost in the prior art, and the joint shape of the specimens is difficult to control, which limits the depth and breadth of research on the mechanical properties of rocks.
The pre-jointed microcrystalline wax material is used, and the pre-jointed microcrystalline wax material is heated through a water bath to make it liquid, poured into the joint mold for cooling and setting, and the pre-jointed microcrystalline wax medium is obtained. Then the rock-like material and pre-jointed microcrystalline wax medium are loaded into the test piece mold respectively. After vibration exhaust and curing, the microcrystalline wax medium is removed by water bath and ether treatment to form a rock-like test with controllable joints. .
It realizes the preparation of rock-like specimens with low cost and simple operation, which can more naturally conform to the internal development of joint cracks, improves the breadth and depth of rock mechanics research, and is suitable for the analysis and research of actual rock mechanics problems in engineering.
Smart Images

Figure CN119394756A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of geotechnical engineering, and in particular to a method for preparing a pre-jointed rock specimen. Background Art
[0002] Rock specimens are used as carriers for laboratory research on rock mechanics. They are generally obtained by drilling rocks from original rocks. However, for the preparation of rock specimens with controllable joints, they are mostly prepared by gluing and splicing rock blocks or using rock-like materials such as concrete. The above methods have a certain impact on the integrity of the specimens. At the same time, the process of preparing rock specimens with internal joints is complicated. Secondly, when using rock-like materials, the joints are usually pre-set joints that penetrate the specimens, which results in certain limitations in the analysis of the influence of joints on the mechanical properties of rocks. Non-penetrating joints are very common in engineering. The study of this type of problem often relies on numerical simulation. Laboratories usually need to use 3D printing technology to prepare the corresponding specimens, which increases the cost of the test.
[0003] Based on this, how to achieve low-cost preparation of rock-like specimens with joints while making them more naturally fit the internal development of joint cracks has become a new field of exploration in rock mechanics experiments. Based on the existing rock-like specimen preparation methods, a low-cost, easy-to-operate preparation method for rock-like specimens with controllable joints was invented, which will provide support for the study of rock mechanics problems. Summary of the invention
[0004] In response to the technical problems raised above, a method for preparing a rock specimen with pre-set joints is provided.
[0005] The technical means adopted by the present invention are as follows:
[0006] A method for preparing a pre-jointed rock specimen comprises the following steps:
[0007] Step 1: Select the target original rock for mechanical property testing to obtain the original rock mechanical property indicators, including dynamic indicators and static indicators;
[0008] Step 2: Obtain rock-like materials that meet the requirements based on the mechanical property indicators of the original rock;
[0009] Step 3, pre-treating the pre-jointed microcrystalline wax material to make it in a fluid state, pouring it into a joint preparation mold, and demoulding it after cooling and shaping to obtain a pre-jointed microcrystalline wax medium;
[0010] Step 4: Load a certain amount of rock-like material into the specimen preparation mold, then place the pre-jointed microcrystalline wax medium into the specimen preparation mold, and then continue to load the rock-like material into the specimen preparation mold until it is full, and perform vibration exhaust to obtain a rock-like specimen after shaping;
[0011] Step 5, demoulding and curing the finalized rock-like specimen;
[0012] Step 6, subjecting the cured rock-like specimen to a water bath treatment to melt the pre-set joint microcrystalline wax medium and discharge it from the rock-like specimen;
[0013] Step 7: Process the rock-like specimens according to the test requirements and conduct corresponding test analysis and research.
[0014] Furthermore, in step 1, the original rock mechanical property indicators include physical and mechanical parameter indicators of uniaxial compressive strength, shear strength, triaxial compressive strength, dynamic compressive strength, and dynamic tensile strength.
[0015] Furthermore, in step 2, according to the mechanical property indicators of the original rock, rock-like materials are configured and test samples are prepared, the mechanical properties of the rock-like materials are tested and obtained, and the material ratio is adjusted to obtain rock-like materials that meet the requirements; wherein the ratio of the rock-like materials and the original rock satisfies the three similarity theorems, including geometric similarity, physical similarity, and single-valued conditional similarity.
[0016] Furthermore, in step 3, the solid microcrystalline wax is pre-heated by heating in a water bath at a temperature of 95° C. or above until the microcrystalline wax is in liquid state; the forming size of the pre-jointed microcrystalline wax medium is not larger than the rock specimen preparation mold in the radial direction and is complete and continuous.
[0017] Furthermore, in step 4, the aspect ratio of the specimen preparation mold is not less than 2. When the rock-like material is loaded into the mold to 1 / 5-1 / 4, the pre-set joint microcrystalline wax medium is inserted, and the pre-set joint microcrystalline wax medium is avoided when continuing to load the rock-like material; after the specimen preparation mold is filled, ensure that the pre-set joint microcrystalline wax medium has at least one exposed rock specimen surface; the vibration frequency of the vibration exhaust is 50-200Hz.
[0018] Furthermore, in step 5, a curing plan is determined according to the rock-like material, including water-retaining curing, covering curing or coating curing, and the curing time at room temperature is 7-28 days.
[0019] Furthermore, in step 6, during the water bath treatment, the rock-like specimen is immersed in a water bath environment with a water temperature above 95°C. When the microcrystalline wax no longer floats on the water surface, the water bath environment is maintained for more than 5 minutes. The total time of the water bath treatment is not less than 20 minutes.
[0020] Furthermore, when the rock-like specimen after the water bath treatment in step 6 does not meet the test requirements, the rock-like specimen after the water bath treatment is placed in an ether solution to soak and dissolve the pre-set joint microcrystalline wax medium to ensure the effective formation of the joints of the rock-like specimen.
[0021] Furthermore, when using ether to clean the specimens, the rock-like specimens were fully immersed in the ether solution, sealed and left to stand for more than 30 minutes, the rock-like specimens were taken out and rinsed with clean water. During the process, the room was kept ventilated, the room temperature was controlled below 20°C, and protective gear was worn.
[0022] Furthermore, in step 7, when injecting a medium other than the pre-set joint microcrystalline wax medium into the joint, the fluidity and particle size of the medium are ensured so that the medium can be injected into the joint, thereby improving the reliability of the test.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1. The present invention uses amorphous microcrystalline wax materials in the treatment of pre-set joint media. Under water bath heating conditions, it can be converted from solid to liquid, soluble in ether, and is easy to separate from rock-like materials without affecting the properties of the rock-like materials themselves. Through this improvement, it can effectively solve the problem that the solid medium used in the conventional specimen preparation process cannot pre-set non-penetrating complex joints or the complex joint pre-set materials cannot be removed, and other media can be placed in the joints where the microcrystalline wax is removed to carry out the study of the mechanical properties of joints with different fillings, which can effectively improve the breadth and width of rock mechanics research.
[0025] 2. The present invention can achieve controllable internal joint morphology of the specimen as much as possible and not fully penetrate the specimen to better fit the engineering situation where the internal joints are well developed but there are no obvious cracks on the surface, including the steps of testing the mechanical properties of the original rock, proportioning of similar materials, preparation of pre-set joint media, mold placement of similar materials and joint media and vibration exhaust, specimen maintenance, water bath removal of joint media, ether immersion removal of impurities, specimen polishing and the like. The pre-set joint specimens prepared by the above steps will be more convenient for the analysis and research of some actual rock mechanics problems in engineering.
[0026] Based on the above reasons, the present invention can be widely promoted in fields such as geotechnical engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 Flow chart of the method of the present invention.
[0029] Figure 2It is a schematic diagram of the surface of the rock specimen with exposed joint medium of the present invention, wherein 1 and 3 are pre-set joint specimens, 1-A and 3-A are schematic diagrams of the corresponding cross-sections of the specimens, and 2 is the surface position of the rock specimen with exposed joint medium.
[0030] Figure 3 Schematic diagram of the mold assembly of rock specimens containing pre-set joints in Example 1 of the present invention, wherein (a)(a) is the main view and (b) is the cross-sectional view of (a).
[0031] Figure 4 Schematic diagram of the mold assembly of rock specimens containing pre-set joints in Example 2 of the present invention, wherein (a)(a) is the main view and (b) is the cross-sectional view of (a). DETAILED DESCRIPTION
[0032] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0035] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values of the parts and steps set forth in these embodiments do not limit the scope of the present invention. Meanwhile, it should be clear that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, and therefore, once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.
[0036] The present invention provides a method for preparing a rock specimen with pre-set joints, which can achieve controllable joint morphology inside the specimen as much as possible and not fully penetrate the specimen to better fit the engineering situation where the internal joints are developed but there are no obvious cracks on the surface. The method includes the following steps: testing the mechanical properties of the original rock, proportioning similar materials, making a pre-set joint medium, putting similar materials and joint medium into a mold and vibrating and exhausting, specimen curing, removing the joint medium in a water bath, soaking in ether to remove impurities, specimen polishing, etc. The pre-set joint specimen prepared by the above steps will be more convenient for analyzing and studying some actual rock mechanics problems in some engineering projects.
[0037] A method for preparing a pre-jointed rock specimen of the present invention comprises the following steps:
[0038] Step 1: Before preparing the rock-like specimen, the target original rock must be selected for mechanical property testing, and the dynamic and static indicators must be determined and recorded;
[0039] Step 2: Proportioning similar materials according to the recorded original rock mechanical property indicators;
[0040] Step 3, pre-treating the pre-jointed microcrystalline wax material to make it in a fluid state, pouring it into a joint preparation mold, and demoulding it after cooling and shaping to obtain a pre-jointed microcrystalline wax medium;
[0041] Step 4: When a certain proportion of the prepared rock-like material is loaded into the specimen preparation mold, the pre-set joint microcrystalline wax medium is placed in the specimen preparation mold, and then the rock-like material is continuously loaded into the specimen preparation mold, and the rock-like material is vibrated and exhausted, and the rock-like specimen is obtained after shaping;
[0042] Step 5, demoulding and curing the shaped rock-like specimen;
[0043] Step 6, subjecting the cured rock-like specimen to a water bath treatment to melt the pre-set joint microcrystalline wax medium and discharge it from the rock-like specimen;
[0044] Step 7: If necessary, the rock-like specimen after water bath treatment can be placed in an ether solution to soak and dissolve the joint medium to ensure the effective formation of the specimen joints.
[0045] Step 8: According to the specific requirements of relevant tests for rock-like specimens, the cleaned specimens are processed and corresponding test analysis and research are carried out.
[0046] Preferably, in step 1, the dynamic and static indicators include but are not limited to physical and mechanical parameter indicators such as uniaxial compressive strength, shear strength, triaxial compressive strength, dynamic compressive strength, and dynamic tensile strength.
[0047] Preferably, in step 2, the similar material ratio result used and the original rock must satisfy the three similarity theorems, including geometric similarity, physical similarity, and single-valued condition similarity.
[0048] Preferably, in step 3, the solid microcrystalline wax is heated by water bath heating, and the water bath temperature is above 95° C. until the microcrystalline wax is in liquid state; the shape of the joint mold used can be customized in advance, and the forming size of the joint medium in the radial direction is not larger than the rock specimen preparation mold and is complete and continuous.
[0049] Preferably, in step 4, when the rock-like material is loaded to 1 / 5-1 / 4 of the mold itself, the aspect ratio of the mold is not less than 2, the joint medium is placed, and the joint medium needs to be avoided when continuing to load similar materials. When the specimen preparation mold is completed, it is necessary to ensure that the joint medium has at least one exposed rock specimen surface. The vibration frequency during vibration exhaust needs to be adjusted according to the specific similar material, generally at 50-200Hz.
[0050] Preferably, in step 5, a curing plan is determined according to the specific conditions of the rock-like material, including water-retaining curing, covering curing or coating curing, and the curing time at room temperature is 7-28 days.
[0051] Preferably, in step 6, ensure that the rock-like specimen is immersed in a water bath environment with a water temperature above 95°C, and maintain the water bath environment for more than 5 minutes until the microcrystalline wax no longer floats on the water surface. The total water bath time is not less than 20 minutes. If the specimen meets the test requirements after this step, step 7 can be skipped.
[0052] Preferably, in step 7, when ether is used to clean the test piece, the rock-like test piece is fully immersed in the ether solution, sealed and left to stand for more than 30 minutes, the test piece is taken out and rinsed with clean water. During the process, the room needs to be ventilated, the room temperature needs to be controlled below 20°C, and protective gear needs to be worn.
[0053] Preferably, in step 8, if other media need to be injected into the joints, the fluidity and particle size of the media need to be ensured so that the media can be injected into the joints to improve the reliability of the test.
[0054] The present invention can realize low-cost preparation of rock-like specimens containing joints while making them more naturally consistent with the internal development of joint cracks. This becomes a new field of rock mechanics experimental exploration and provides assistance for the study of rock mechanics problems.
[0055] The present invention can provide new ideas for joint rock mechanics research, large-scale preparation, and improve experimental repeatability.
[0056] Example 1
[0057] A method for preparing a pre-jointed rock specimen comprises the following steps:
[0058] Step 1: Before preparing the rock-like specimen, it is necessary to select the target rock mass as granite and conduct mechanical property tests to determine the dynamic peak compressive strength and uniaxial compressive strength:
[0059] Under specific conditions, the average dynamic peak compressive strength of granite rock was measured to be 196 MPa, and the average uniaxial compressive strength was measured to be 110 MPa using a YAW-2000 pressure servo machine.
[0060] Step 2: Based on the three similarity theorems and the measured granite original rock mechanical data, similar rock materials are configured to prepare test standard samples, and the mechanical properties of the similar rock materials are measured. The proportion of similar materials is adjusted to make the similar rock materials meet the requirements;
[0061] Step 3. Put 70# microcrystalline wax particles into a beaker, place it in a water bath environment, keep the water temperature constant at 96°C, and stir the microcrystalline wax continuously until the microcrystalline wax particles are completely converted into liquid; put the microcrystalline wax liquid into an "X"-shaped conjugate joint mold with adjustable length, and after natural cooling, demold and remove the microcrystalline wax joint medium for use.
[0062] Step 4: Place the well-proportioned rock-like material into the 1 / 4 of the mold with a length-to-diameter ratio of 2, add the microcrystalline wax joint medium, and ensure that the joint medium is connected to the mold at one point (such as Figure 3 As shown), so that the joint medium has at least one exposed surface of the rock-like specimen after molding, continue to load the specimen mold with rock-like materials until it is full; place the assembled mold on a vibration table for exhaust vibration, and set the vibration frequency to 55 Hz.
[0063] Step 5: Based on the similar characteristics of rock-like materials, determine the maintenance plan to retain water at room temperature for 28 days.
[0064] Step 6: De-mould the cured specimens and place them in a water bath. Immerse the specimens in water at 95°C until the microcrystalline wax no longer floats on the water surface. Continue in the water bath for 5 minutes. The total water bath time is 35 minutes. Take out the specimens for testing. The test requirements have been met, so skip step 7.
[0065] Step 8: According to the SHPB test requirements, the specimens are processed to prepare several preset specimens with length-to-diameter ratios of 0.5 and 1.0, and corresponding test analysis and research are carried out.
[0066] Example 2
[0067] A method for preparing a pre-jointed rock specimen comprises the following steps:
[0068] Step 1: Before preparing the rock-like specimen, the target rock mass must be selected as phyllite, and the mineral composition analysis and mechanical property test must be performed to determine the dynamic peak compressive strength and uniaxial compressive strength:
[0069] Under specific conditions, the average dynamic peak compressive strength of the phyllite original rock was measured to be 145MPa, and the average uniaxial compressive strength was measured to be 102MPa using the YSD-1 micro-controlled rock servo machine.
[0070] Step 2: Based on the three similarity theorems and the measured phyllite original rock mechanical data, similar rock materials are configured to prepare test standard samples, and the mechanical properties of the similar rock materials are measured. The proportion of similar materials is adjusted to make the similar rock materials meet the requirements;
[0071] Step 3. Put 80# microcrystalline wax particles into a beaker, place it in a water bath environment, keep the water temperature constant at 95°C, and stir the microcrystalline wax continuously until the microcrystalline wax particles are completely converted into liquid; put the microcrystalline wax liquid into a "multi-branch" type length-adjustable joint mold, and after natural cooling, demold and remove the microcrystalline wax joint medium for use.
[0072] Step 4: Place the well-proportioned rock-like material into the 1 / 5 position of the mold with a length-to-diameter ratio of 2, add the microcrystalline wax joint medium, and ensure that the joint medium is exposed from the mold opening or is flush with the mold opening (such as Figure 4 As shown), so that the joint medium has at least one exposed surface of the rock-like specimen after molding, continue to load the specimen mold with rock-like materials until it is full; place the assembled mold on a vibration table for exhaust vibration, and set the vibration frequency to 60 Hz.
[0073] Step 5: Based on the similar characteristics of rock-like materials, determine the maintenance plan to retain water at room temperature for 28 days.
[0074] Step 6: De-mould the cured specimen and place it in a water bath at 95°C. Wait until the microcrystalline wax no longer floats on the water surface and continue the water bath for 5 minutes. The total water bath time is 40 minutes, and then take out the specimen.
[0075] Step 7. Since the pre-set joints of the specimen are relatively complex, in order to ensure that there is no microcrystalline wax residue in the specimen, the specimen is fully immersed in ether solution, sealed and left to stand for 35 minutes. During this period, the indoor temperature is kept constant at 18°C and ventilation is maintained. Then the specimen is taken out.
[0076] Step 8. According to the test requirements, fine cement mortar is injected into some specimens along the joint exposure ports. After solidification and curing, several specimens are polished and prepared into flatness-compliant specimens according to triaxial test conditions, and experimental analysis and research on different joint media are carried out.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a pre-jointed rock specimen, characterized in that: The steps include: Step 1: Select the target original rock for mechanical property testing to obtain the original rock mechanical property indicators, including dynamic indicators and static indicators; Step 2: Obtain rock-like materials that meet the requirements based on the mechanical property indicators of the original rock; Step 3, pre-treating the pre-jointed microcrystalline wax material to make it in a fluid state, pouring it into a joint preparation mold, and demoulding it after cooling and shaping to obtain a pre-jointed microcrystalline wax medium; Step 4: Load a certain amount of rock-like material into the specimen preparation mold, then place the pre-jointed microcrystalline wax medium into the specimen preparation mold, and then continue to load the rock-like material into the specimen preparation mold until it is full, and perform vibration exhaust to obtain a rock-like specimen after shaping; Step 5, demoulding and curing the finalized rock-like specimen; Step 6, subjecting the cured rock-like specimen to a water bath treatment to melt the pre-set joint microcrystalline wax medium and discharge it from the rock-like specimen; Step 7: Process the rock-like specimens according to the test requirements and conduct corresponding test analysis and research.
2. The method for preparing a pre-jointed rock specimen according to claim 1, characterized in that: In step 1, the original rock mechanical property indicators include physical and mechanical parameter indicators of uniaxial compressive strength, shear strength, triaxial compressive strength, dynamic compressive strength, and dynamic tensile strength.
3. The method for preparing a pre-jointed rock specimen according to claim 1, characterized in that: In the step 2, according to the mechanical property index of the original rock, the rock-like material is configured and the test standard sample is prepared, the mechanical properties of the rock-like material are obtained by testing, and the material ratio is adjusted to obtain the rock-like material that meets the requirements; wherein the ratio of the rock-like material and the original rock satisfies the three similarity theorems, including geometric similarity, physical similarity, and single-valued conditional similarity.
4. The method for preparing a pre-jointed rock specimen according to claim 1, characterized in that: In the step 3, the solid microcrystalline wax is preheated by heating in a water bath at a temperature of 95° C. or above until the microcrystalline wax is in liquid state; the forming size of the pre-jointed microcrystalline wax medium is not larger than the rock specimen preparation mold in the radial direction and is complete and continuous.
5. The method for preparing a pre-jointed rock specimen according to claim 1, characterized in that: In step 4, the aspect ratio of the specimen preparation mold is not less than 2. When the rock-like material is filled to 1 / 5-1 / 4 in the mold, the pre-set joint microcrystalline wax medium is inserted, and the pre-set joint microcrystalline wax medium is avoided when continuing to fill the rock-like material; after the specimen preparation mold is filled, ensure that the pre-set joint microcrystalline wax medium is exposed on the surface of the rock-like specimen at least at one place; the vibration frequency of the vibration exhaust is 50-200Hz.
6. The method for preparing a pre-jointed rock specimen according to claim 1, characterized in that: In step 5, a curing plan is determined according to the rock-like material, including water-retaining curing, covering curing or coating curing, and the curing time at room temperature is 7-28 days.
7. The method for preparing a pre-jointed rock specimen according to claim 1, characterized in that: In step 6, during the water bath treatment, the rock-like specimen is immersed in a water bath environment with a water temperature of more than 95° C. When the microcrystalline wax no longer floats on the water surface, the water bath environment is maintained for more than 5 minutes. The total time of the water bath treatment is not less than 20 minutes.
8. The method for preparing a pre-jointed rock specimen according to claim 1, characterized in that: When the rock-like specimen after the water bath treatment in step 6 does not meet the test requirements, the rock-like specimen after the water bath treatment is placed in an ether solution to soak and dissolve the pre-set joint microcrystalline wax medium to ensure the effective formation of the joints of the rock-like specimen.
9. The method for preparing a pre-jointed rock specimen according to claim 8, characterized in that: When using ether to clean the specimen, fully immerse the rock-like specimen in the ether solution, seal it and let it stand for more than 30 minutes, take out the rock-like specimen and rinse it with clean water. During the process, keep the room ventilated, control the room temperature below 20℃ and wear protective gear.
10. The method for preparing a pre-jointed rock specimen according to claim 1, characterized in that: In step 7, when injecting a medium other than the pre-set joint microcrystalline wax medium into the joint, ensure the fluidity and particle size of the medium so that the medium can be injected into the joint and the reliability of the test is improved.